Architectural Interpretations of Qur’anic and Hadith Influences in Traditional Indonesian Mosques During the Walisanga Era - Fikriyati, Ulya (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2023)
This research investigates the reception of the Qur’ān within the realm of mosque architecture, traditionally assessed through the study of text integrated into mosque ornamentation. This article introduces a reception studies to Walisanga mosques architecture, encompassing considerations of spatial design, essence, illumination, and interior ambiance. Notably, this study diverges from conventional methods by abstaining from the inclusion of Qur’anic or hadith text. The primary objectives of this article are twofold: a) to elucidate the relationship between the architecture of traditional Indonesian mosques and the Qur’an and Hadith, and b) to unveil how architectural elements within traditional mosques visually interpret QS. 24:35 and the Hadith of Gabriel. In order to achieve a comprehensive analysis, this study employs both semantic and hermeneutic methodologies. The semantic approach is applied to dissect the atomistic structure of QS. 24:35 and the Hadith of Gabriel, with the intent of identifying foundational components that underpin the concept of tajug tumpang in traditional Indonesian mosque architecture. Subsequently, a hermeneutic approach is adopted to explore the interconnection between the verse QS. 24:35, the Hadith of Gabriel, and their architectural manifestations within the context of traditional Indonesian mosque construction.The result of the analysis culminates in the identification of two primary forms of architectural reception of QS. 24:35 and the Hadith of Gabriel within traditional Indonesian mosques. Firstly, instances wherein the textual meanings are directly translatable are actualized through elements such as light, lanterns, trees, and niches, all tailored to the Indonesian cultural milieu. Secondly, fundamental concepts derived from the Qur’an and Hadith, which resist tangible representation, are reinterpreted and incorporated into facets of spatial arrangement, lighting schemes, colour selections, ornamental details, and the harmonization of additional components, all resonating harmoniously with the Indonesian cultural identity.